Knowledge Regarding Prevention of Urinary Tract Infection In Patients with Indwelling Catheter among Staff Nurses: An Interventional Study - Surinder Singh; Ruchi Kumari; Aarti Thakur; Sakshi Tomar; Mridul (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study based on a broad framework with input, throughput, output and feedback first presented byLudwing Von Bertalanffy. The investigation utilised an evaluative approach. Samples of 50 staff nurseswere collected using random sampling by lottery. A structured questionnaire was used for data collection.The overall pre-test knowledge mean score was 14.14±1.629. After administration of the self-instructionalmodule, the post-test mean score increased to 20.56±4.362. The hypothesis H1 expressed that there will bea considerable distinction between pre-test and post-test information scores of nursing officers regardingurinary tract infection. The 't ' test was discovered to be more prominent than the table worth. Acquiredworth was (10.353), and table worth was (2.045). It showed the effectiveness of the SIM. The study wasno significant relationship with demographic variables because the chi- square value was less than the tablevalue. Thus, the H2 has been dismissed.